2015
DOI: 10.1108/meq-01-2014-0010
|View full text |Cite
|
Sign up to set email alerts
|

Field burning practices in a southern region of Brazil

Abstract: Purpose – The practice of field burning has been used for many years in the south regions of Brazil as an ideal way to maintain pastures. The purpose of this paper is to understand if such activity is logically explicable or if it is the result of a cultural reality, being “prisoner” of this technique because of path dependence, within the paradigm of the path dependence theory. Design/methodology/approach – This present research is expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…59 publications discuss how attitudinal and cultural factors are a key determinant in the propensity of individuals to behave and act differently in relation to technology adoption, food consumption habits, and their willingness to ignore or proactively address negative environmental externalities of agri-food systems. This explainations appears most frequently in publications belonging to the AS and STS research domains, arguing that values, attitudes, cultures create a lock-in that keeps actors stuck in certain production and consumption modes (Barnes et al, 2016;Beilin et al, 2012;Bonke and Musshoff, 2020;V De Herde et al, 2019;Gonçalves et al, 2015;IPES, 2016;Reenberg et al, 2012;Renwick et al, 2019;Stassart and Jamar, 2008;Wilson, 2008). For example, for farmers, this means that after the initial adoption of a certain cropping practice, the practice becomes part of the family tradition, and thus is automatically labelled as the "best" one -even when it endangers negative externalities (Gonçalves et al, 2015).…”
Section: Attitudes and Cultures That Cause Aversion To Changementioning
confidence: 97%
See 2 more Smart Citations
“…59 publications discuss how attitudinal and cultural factors are a key determinant in the propensity of individuals to behave and act differently in relation to technology adoption, food consumption habits, and their willingness to ignore or proactively address negative environmental externalities of agri-food systems. This explainations appears most frequently in publications belonging to the AS and STS research domains, arguing that values, attitudes, cultures create a lock-in that keeps actors stuck in certain production and consumption modes (Barnes et al, 2016;Beilin et al, 2012;Bonke and Musshoff, 2020;V De Herde et al, 2019;Gonçalves et al, 2015;IPES, 2016;Reenberg et al, 2012;Renwick et al, 2019;Stassart and Jamar, 2008;Wilson, 2008). For example, for farmers, this means that after the initial adoption of a certain cropping practice, the practice becomes part of the family tradition, and thus is automatically labelled as the "best" one -even when it endangers negative externalities (Gonçalves et al, 2015).…”
Section: Attitudes and Cultures That Cause Aversion To Changementioning
confidence: 97%
“…This explainations appears most frequently in publications belonging to the AS and STS research domains, arguing that values, attitudes, cultures create a lock-in that keeps actors stuck in certain production and consumption modes (Barnes et al, 2016;Beilin et al, 2012;Bonke and Musshoff, 2020;V De Herde et al, 2019;Gonçalves et al, 2015;IPES, 2016;Reenberg et al, 2012;Renwick et al, 2019;Stassart and Jamar, 2008;Wilson, 2008). For example, for farmers, this means that after the initial adoption of a certain cropping practice, the practice becomes part of the family tradition, and thus is automatically labelled as the "best" one -even when it endangers negative externalities (Gonçalves et al, 2015). A study in Brazil revealed how field burning practices in are still employed in spite of their negative environmental externalities, as they have become part of the family history, and thus farmers do not want to detach from them.…”
Section: Attitudes and Cultures That Cause Aversion To Changementioning
confidence: 97%
See 1 more Smart Citation
“…Educational challenges are associated with "attitudes and cultures that cause aversion to change" and "research priorities, practices and dominant innovation narratives misaligned to the transformational change agenda". When certain practices are adopted and considered as part of the family tradition, they are automatically labelled as the "best" ones [103]. Finally, policy challenges emerge from "misaligned institutional settings, policies and incentives" and "political economy factors that skew the direction of change".…”
Section: Rq4: What Are the Challenges Of Implementing Industry 40 In An Afsc?mentioning
confidence: 99%